The received view and Revelation: A social-scientific reading of Revelation 2–3 - van Niekerk, Robert J.; van Eck, Ernest (Verbum et ecclesia, 2024)
This article aims to present a culturally plausible reading of Revelation 2–3. This will be done through the use of a social-scientific model focussing on the core values of honour and shame in the ancient Mediterranean world. Before describing this model, the article will present a cursory discussion on the currently received view of Revelation’s genre and Revelation 2–3. It is argued that while the received view provides valuable historical descriptions of the ancient Mediterranean world, this approach is inadequate to bring to the fore the underlying norms and values found in Revelation 2–3. Using the model of honour and shame as a lens through which to read Revelation 2–3, it becomes apparent that these seven letters are filled with honour claims that are either confirmed, challenged or denied. In addition, honour is also ascribed to specific communities, and in some cases, honour is redefined.Intradisciplinary and/or interdisciplinary implicationsReading Revelation 2–3 through social-scientific models engages critically with the traditional approach to these texts, and provides a culturally sensitive and responsible reading thereof. This reading further promotes a constructive engagement with cross-cultural anthropology.